Empowering the Community through Household Waste Source Separation Education in Barengkok Village: A Pretest–Posttest Evaluation - Ramadhani, Adhitya Ryan; Kadarno, Purwo; Pradanawati, Sylvia Ayu; Riyandwita, Byan Wahyu; Barrinaya, Muhammad Akbar; Pranowo, Waskito; Nugroho, Herminarto (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance the knowledge and skills of residents in Barengkok Village regarding household waste segregation at the source, particularly the separation of organic and inorganic waste, as well as basic on-site processing of organic waste at the household level. The implementation method employed a participatory educational approach through training sessions involving adult residents as the primary participants. The program integrated participatory instruction, hands-on demonstrations, including the establishment of a two-bin waste separation system and basic composting techniques, and pre- and post-assessments consisting of seven waste literacy items. Descriptive statistics indicated consistent post-session improvement across all items, with the most substantial gains observed in waste categorization and organic waste management skills. Participant surveys revealed very high perceived relevance and satisfaction, suggesting that the program was well received by the community. This initiative provides a practical and cost-effective model that combines clear procedures with simple supporting tools, including designated two-bin kits and a laminated kitchen guide, enabling households to operate more independently despite downstream collection limitations. The findings also suggest the need for a brief 4–6-week follow-up period, including bin placement monitoring, contamination assessment, and initial compost trials, as well as a strategy for village-level institutionalization through community advocates and a regular buy-back schedule for clean recyclables.